A Single-Center Experience of the Optimal Initial Immunosuppressive Strategy for Preventing Early Acute Cellular Rejection in Orthotopic Heart Transplantation Associated With Renal Dysfunction. (December 2019) - Mundisugih, Juan; Fernando, Himavan; Bergin, Peter; Hare, James; Kaye, David; Leet, Angeline; McGiffin, David; Taylor, Andrew J.
Background: Renal dysfunction is a common complication following heart transplantation that may be worsened by the early initiation of calcineurin inhibitors. Antithymocyte globulin (ATG) or basiliximab has been used to delay or avoid calcineurin inhibitors. The most effective strategy for preventing early acute cellular rejection in this context is uncertain. Methods: We retrospectively reviewed all heart transplant cases between January 2012 and June 2017. The standard therapy consisted of mycophenolate mofetil, prednisolone, and tacrolimus. In patients at high risk of post-transplant renal dysfunction, an early calcineurin inhibitor-free regimen with basiliximab and/or ATG was used. Patients were assigned to cohorts based on the initial immunosuppressive strategy. The primary end point was the freedom rate of acute cellular rejection within 4 weeks post-transplant. Results: Of 93 cases, 21 patients received standard therapy, 64 patients received an initial calcineurin inhibitor-free regimen with basiliximab, and 8 patients received ATG and basiliximab. Freedom from acute rejection was greater in the ATG plus basiliximab group (all rejection free), compared to 40 (63%) of 64 patients treated with basiliximab and 10 (48%) of 21 patients treated with standard therapy ( P < .05, log rank test). In patients treated with basiliximab, early administration (<24 hours) was associated with a higher freedom from acute rejection compared to ≥24 hours, (72% vs 29%, P < .05). Conclusions: The combination of ATG and basiliximab was more effective in preventing acute cellular rejection. In those patients treated with basiliximab, rejection rates were no worse than standard therapy; however, it was only effective when administered within 24 hours.